Predominant contralateral ocular symptoms in a right caroticocavernous fistula: a rare case report - PAVITRA VIJAYAN; WAN MOHAMMAD IBRAHIM WAN AZMAN; KHAIRUL AZMI ABDUL KADIR (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Caroticocavernous fistula (CCF) is an unusual communication between the carotid artery and cavernous sinus (CS), leading to myriad of ipsilateral ocular symptoms, including ocular congestion, venous hypertension and ophthalmoplegia. While bilateral ocular involvement is recognized, predominantly contralateral ocular symptoms are exceptionally rare. To date, only a single case of contralateral ocular symptom secondary to ipsilateral CCF has been reported in the literature worldwide. We present a second such case, with symptoms progression occurring over a four-month period following head trauma. Early diagnosis is crucial to prevent complications and morbidity. Case presentation A 76-year-old female sustained multiple intracranial haemorrhages without evidence of skull fractures following a misstep. A week later, family members noticed bilateral eye squinting, however did not seek medical treatment. Three months later, an ophthalmology assessment revealed bilateral cranial nerve VI palsy, which was attributed to traumatic brain injury and managed conservatively. One month after that, the patient developed worsening left-sided ocular symptoms, including redness, proptosis and increased intraocular pressure. Computed tomography angiogram (CTA) revealed bulky bilateral CS and dilated left superior ophthalmic vein (SOV). Digital subtraction angiography (DSA) unexpectedly demonstrated a right-sided direct CCF with contralateral involvement of left SOV. No left-sided CCF was noted. Transvenous embolization of the right CCF led to an improvement in left eye symptoms. Conclusion This case underscores the need for vigilance in patients post-trauma with ocular symptoms, the importance of advanced vascular imaging when CCF is suspected and the effectiveness of transvenous embolization in managing direct CCFs. The progressive nature of CCFs emphasizes the necessity of long-term monitoring to ensure timely diagnosis and treatment, thereby preventing further complications.